2019
DOI: 10.1186/s12879-019-4469-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous 18F-FDG PET/MRI in tuberculous spondylitis: an independent method for assessing therapeutic response - case series

Abstract: Background 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) shows great potential for diagnosis and assessing therapeutic response of tuberculous spondylitis. Tuberculous spondylitis required long-term anti-tuberculosis (TB) medication therapy, and the optimal duration of therapy is controversial. There is still no clear way to tell when the anti-TB therapy can safely be discontinued. Case presentation Three patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In particular, 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) was used to analyze the metabolic characteristics of cured PVO lesion, and the results were compared with the clinical features and MRI findings. Recently, studies related to the use of FDG-PET to assess therapeutic response in spine infection have been reported; this approach can be less affected by the other conditions than hematological inflammatory indices [ 9 , 10 , 11 ]. Although FDG-PET has merit in identifying metabolic changes in infectious conditions, it has limited ability to visualize anatomical changes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) was used to analyze the metabolic characteristics of cured PVO lesion, and the results were compared with the clinical features and MRI findings. Recently, studies related to the use of FDG-PET to assess therapeutic response in spine infection have been reported; this approach can be less affected by the other conditions than hematological inflammatory indices [ 9 , 10 , 11 ]. Although FDG-PET has merit in identifying metabolic changes in infectious conditions, it has limited ability to visualize anatomical changes.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent spatial resolution combined with metabolic evolution and reduced overall patient radiation dose is a few of the important advantages in comparison to PET/CT. [ 11 ] Cost is the only limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…In the assessment of therapeutic response in spine infection, the attempts to apply 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET) have been going on for 10 years, and detailed research results have been reported [ 10 , 11 ]. 18 F-FDG-PET is considered to be less affected by other conditions than blood inflammatory markers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%